2021
DOI: 10.3201/eid2710.211500
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Delta Variant among Asiatic Lions, India

Abstract: In May 2021, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was detected in Asiatic lions in a zoological park in India. Sequence and phylogenetic analyses showed the SARS-CoV-2 strains were the B.1.617.2 (Delta) variant. To reduce transmission of variants of concern, surveillance of SARS-CoV-2 in wild animal populations should be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 6 publications
3
57
0
2
Order By: Relevance
“…These facts, together with the growing number of cats that are kept as pets, cat colonies in urban scenarios and the abundance of feral cats throughout the world, make it imperative to examine the role of this species in the current COVID-19 pandemic. Not only cats, but also large wild felines such as tigers and lions have also been naturally infected by SARS-CoV-2 (McAloose et al 2020), including the delta variant in Asiatic lions (Mishra et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These facts, together with the growing number of cats that are kept as pets, cat colonies in urban scenarios and the abundance of feral cats throughout the world, make it imperative to examine the role of this species in the current COVID-19 pandemic. Not only cats, but also large wild felines such as tigers and lions have also been naturally infected by SARS-CoV-2 (McAloose et al 2020), including the delta variant in Asiatic lions (Mishra et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…S1A, S5H). The 203M/452R and Delta variants appeared as early as March 2020 and May 2020 29 , respectively (Fig. S5G, H).…”
Section: Resultsmentioning
confidence: 99%
“…In hamsters, higher shedding of subgenomic RNA has been reported for 14 days, and moderate lung pathology has been reported in 40% of infected animals [ 9 ]. Delta can cause vaccine breakthrough events in humans [ 10 ] and has been reported to infect Asiatic lions ( Panthera leo persica ) in Arignar Anna Zoological Park, Chennai, Tamil Nadu, India [ 11 ]. Analysis of an outbreak involving 167 cases from China showed that the time interval between exposure to first positive PCR was shorter (4 vs 6 days), the initial viral load 1260-folds higher and more infectious (80% vs. 19% harbouring > 6 × 10^5 viral copies/ml) than in 19A/19B infection: some minor intra-host single nucleotide variants (iSNVs) could be transmitted between hosts and finally fixed in the virus population during the outbreak.…”
Section: Discussionmentioning
confidence: 99%